2012
DOI: 10.1155/2012/740671
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Green Tea Extract against Hepatic Tissue Injury in Streptozotocin-Induced Diabetic Rats

Abstract: Although diabetic hepatopathy is potentially less common, it may be appropriate for addition to the list of target organ conditions related to diabetes. This study was designed to evaluate the hepatoprotective properties of green tea extract (GTE) in STZ-induced diabetes in rats. Wistar rats were made diabetic through single injection of STZ (75 mg/kg i.p.). The rats were randomly divided into four groups of 10 animals each: Group 1, healthy control; Group 2, nondiabetics treated with GTE administered orally (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 65 publications
7
53
1
3
Order By: Relevance
“…Such agents include sulphonylureas and biguanides, despite the report on their negative effects. Therefore, in searching for alternative agent that will be cheaper and safer, attention has now been focused on the use of medicinal plants for the management of diabetes disease ( [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Such agents include sulphonylureas and biguanides, despite the report on their negative effects. Therefore, in searching for alternative agent that will be cheaper and safer, attention has now been focused on the use of medicinal plants for the management of diabetes disease ( [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Mateos reported that, fruit powders rich in phenolic compounds are very effective in reducing lipid peroxidation in hypercholesterolaemic rats [29]. Furthermore, oral feeding of green tea reduces hyperlipidemia and enhances the activities of SOD and CAT in rats [30]. These studies revealed that beneficial effects of phenolic compounds maybe mediated by one or more mechanisms such as by inhibiting lipid peoxidation, platelet aggregation and enhancing of antioxidant defense.…”
Section: Discussionmentioning
confidence: 96%
“…Elevated serum MDA levels are considered to be an indicator of cellular membrane injury caused by oxidative stress 30 . Many studies have reported on diminished enzymatic and non-enzymatic antioxidant activities in diabetic rats 31,32 . Oxidative stress resulting from excessive production of ROS has been suggested to be a potential mechanism involved in diabetic hepatopathy 32 and other complications 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on diminished enzymatic and non-enzymatic antioxidant activities in diabetic rats 31,32 . Oxidative stress resulting from excessive production of ROS has been suggested to be a potential mechanism involved in diabetic hepatopathy 32 and other complications 33,34 . In the current study, the administration of aqueous extract of MC berries provided a significant improvement in the antioxidant system, namely an increment in SOD activity and GSH levels and a reduction in MDA levels.…”
Section: Discussionmentioning
confidence: 99%